2016
DOI: 10.1021/acsami.6b11011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Optoelectronic Quality of Hybrid Perovskites by Conductive Atomic Force Microscopy with Noise Spectroscopy

Abstract: Organic-inorganic hybrid perovskite solar cells have emerged as promising candidates for next-generation solar cells. To attain high photovoltaic efficiency, reducing the defects in perovskites is crucial along with a uniform coating of the films. Also, evaluating the quality of synthesized perovskites via facile and adequate methods is important as well. Herein, CHNHPbI perovskites were synthesized by applying second solvent dripping to nonstoichiometric precursors containing excess CHNHI. The resulting perov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 54 publications
2
50
1
Order By: Relevance
“…The local DC current is detected by a high sensitivity current sensor connected to the tip. [39] even under different operating conditions (illumination). However, due to the nanoscale size of the contact (tip radius ≈10 nm), the first two resistive terms are largely dominating, making possible to extract local information on the electrical properties of the samples, and to get meaningful (i.e., quantitative) comparisons between different samples.…”
Section: Resultsmentioning
confidence: 99%
“…The local DC current is detected by a high sensitivity current sensor connected to the tip. [39] even under different operating conditions (illumination). However, due to the nanoscale size of the contact (tip radius ≈10 nm), the first two resistive terms are largely dominating, making possible to extract local information on the electrical properties of the samples, and to get meaningful (i.e., quantitative) comparisons between different samples.…”
Section: Resultsmentioning
confidence: 99%
“…[43] On the other hand, Lee et al found that grain boundaries did not consistently produce more or less photocurrent than the grain interiors, when mapping the current of an illuminated CH 3 NH 3 PbI 3 film, both at stoichiometry and with excess CH 3 NH 3 I added to the precursor solution. [42] Similar measurements with a bias applied across the probe tip, however, found that grain boundaries could actually show higher photocurrent at voltages above 0.3 V. [33] This may indicate that at these voltages the external field compensated for the band bending at the grain boundary, thus facilitating charge transport. Yin et al also suggested that chlorine and oxygen could spontaneously segregate into the grain boundaries and passivate those defect levels and deactivate the trap state.…”
Section: Grain Boundaries Passivation and Ion Migrationmentioning
confidence: 91%
“…[42] This difference was not related to the different heights of the grains, but rather to their size, with larger grains providing a higher photocurrent. It was also found that the grains with higher photocurrent showed lower crystallographic defects, indicating that passivation of these defects could lead to higher performing grains.…”
Section: Microstructural Heterogeneitymentioning
confidence: 98%
“…Similar to that in OPV, the morphology of hybrid perovskite films such as grain size, crystallinity, and surface roughness plays important roles in determining perovskite PV device performance. Park and co‐workers found that films prepared using nonstoichiometric precursors showed larger grain size than those using stoichiometric precursors . A linear relationship between the grain size and photocurrent was revealed with c‐AFM, which was explained by reduced defect density in MAI‐rich precursor‐induced large crystalline grains as measured by noise spectroscopy.…”
Section: Energy Conversion Devicementioning
confidence: 99%